2022
DOI: 10.1002/jmri.28157
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation of Gd‐EOB‐DTPA‐Enhanced MRI Radiomics‐Based Nomogram in Small Solitary Hepatocellular Carcinoma (≤3 cm) With Microvascular Invasion: A Two‐Center Study

Abstract: Background Preoperative evaluation of microvascular invasion (MVI) in small solitary hepatocellular carcinoma (HCC; maximum lesion diameter ≤ 3 cm) is important for treatment decisions. Purpose To apply gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA)‐enhanced MRI to develop and validate a nomogram for preoperative evaluation of MVI in small solitary HCC and to compare the effectiveness of radiomics evaluation models based on different volumes of interest (VOIs). Study Type Retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In recent years, due to the progress and rapid developments of various hardware and software technologies, radiomics has gradually developed into a relatively mature discipline or medical image analysis method (1). There are more and more publications on the application of radiomics for the diagnosis, differential diagnosis, treatment options, and prognosis evaluation of many human diseases (11)(12)(13)(14)(15)(16). Among them, Hong et al (13) extracted 10 radiomics features from the contrast-enhanced CT (CECT) images of 241 patients with a bone island or osteoblastic metastasis to establish a random forest (RF) prediction model.…”
Section: Introduction Radiomics and Its Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, due to the progress and rapid developments of various hardware and software technologies, radiomics has gradually developed into a relatively mature discipline or medical image analysis method (1). There are more and more publications on the application of radiomics for the diagnosis, differential diagnosis, treatment options, and prognosis evaluation of many human diseases (11)(12)(13)(14)(15)(16). Among them, Hong et al (13) extracted 10 radiomics features from the contrast-enhanced CT (CECT) images of 241 patients with a bone island or osteoblastic metastasis to establish a random forest (RF) prediction model.…”
Section: Introduction Radiomics and Its Processmentioning
confidence: 99%
“…The results showed that the RF model based on CT was helpful to differentiate bone islands from osteoblastic metastases, and its diagnostic performance was higher than that of inexperienced radiologists but equivalent to that of experienced radiologists. In another study, Tian et al ( 16 ) reported the diagnostic value of preoperative evaluation of microvascular invasion of solitary small hepatocellular carcinoma (HCC) based on nomogram of gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) enhanced MRI. The results indicated that the clinical-radiological-radiomics model achieved the highest diagnostic performance with area under the receiver operating characteristic curves (AUCs) of 0.934, 0.889 and 0.875 for the training, internal and external validation sets, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This approach would capture the three-dimensional (3D) information of the entire tumor and has been proved effective in characterizing the heterogeneity of the tumor by acting as a whole tumor virtual biopsy [17,18] . Numerous studies have demonstrated that radiomics-based models effectively identify the diagnosis and pathological characteristics or predict therapeutic e cacy and prognosis of cancer patients for clinical decisionmaking [19][20][21][22] . Recently, there has been increasing interest in evaluating radiomics patterns of the region surrounding the visible tumor [20,23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that radiomics-based models effectively identify the diagnosis and pathological characteristics or predict therapeutic e cacy and prognosis of cancer patients for clinical decisionmaking [19][20][21][22] . Recently, there has been increasing interest in evaluating radiomics patterns of the region surrounding the visible tumor [20,23,24] . Recurrence or metastasis of HCC is mainly intrahepatic, indicating that the peritumoral liver tissue may be a favorable soil for the spreading hepatoma cells [25] .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JMRI , an article by Tian et al 5 repot on a preoperative prediction performance of Gd‐EOB‐DTPA–enhanced MRI radiomics‐based nomogram for MVI in the patients with small solitary HCC. Radiomics is a method that extracts quantitative and spatial features of images as a number of parameters and clarifying their relationship to factors that may affect image findings, such as MVI 6 .…”
mentioning
confidence: 99%